2001
DOI: 10.1055/s-2001-15722
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of watermelon stomach (GAVE syndrome) by means of endoscopic argon plasma coagulation (APC): Long-term outcome

Abstract: We report on 17 patients with GAVE-syndrome (gastric antral vascular ectasia) treated by means of endoscopic argon plasma coagulation (APC). 16 of 17 patients presented with iron deficiency anemia; transfusion-dependent anemia was noted in 11 patients (65%). Resolution of the gastric angiectasia could be achieved in all patients by endoscopic APC after 1-4 treatment sessions. Endoscopic follow-up revealed recurrence of GAVE in 5 patients (requiring further treatment sessions). Mean pretreatment hemoglobin leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 10 publications
3
40
0
Order By: Relevance
“…There were 10 case series on APC (n ¼ 192) that found 21% of patients (0%-80%) had adverse events, no perforations (0%), 2% (1%-14%) failed therapy with 25% (0%-57%) overall mortality, and 12% (0%-50%) of mortality was therapy or bleeding related (Table 2). [58][59][60][61][62][63][64][65][66][67] There were 10 case series on Nd:YAG therapy (n ¼ 185) that found 20% of patients (0%-51%) had complications, 1.6% (0%-14%) had perforations, 6% (0%-13%) failed therapy, and there was 28% (9%-63%) overall mortality, and 10% (0%-25%) of mortality was therapy or bleeding related. [68][69][70][71][72][73][74][75] A single case series on heater probe (n ¼ 12) found 33% of patients had complications, but there were no perforations, therapy failures, or mortality (0%).…”
Section: Gastric Antral Vascular Ectasiamentioning
confidence: 97%
“…There were 10 case series on APC (n ¼ 192) that found 21% of patients (0%-80%) had adverse events, no perforations (0%), 2% (1%-14%) failed therapy with 25% (0%-57%) overall mortality, and 12% (0%-50%) of mortality was therapy or bleeding related (Table 2). [58][59][60][61][62][63][64][65][66][67] There were 10 case series on Nd:YAG therapy (n ¼ 185) that found 20% of patients (0%-51%) had complications, 1.6% (0%-14%) had perforations, 6% (0%-13%) failed therapy, and there was 28% (9%-63%) overall mortality, and 10% (0%-25%) of mortality was therapy or bleeding related. [68][69][70][71][72][73][74][75] A single case series on heater probe (n ¼ 12) found 33% of patients had complications, but there were no perforations, therapy failures, or mortality (0%).…”
Section: Gastric Antral Vascular Ectasiamentioning
confidence: 97%
“…Despite these advantages, some complications have been reported including bleeding, perforation, and sepsis (10). In addition, Probst et al (11) reported that circumferential scarring of the antrum leads to asymptomatic stenosis 6 months after APC treatment. Dulai and Jensen (12) reported that an initial treatment interval of 4 8 weeks would allow for interim healing of iatrogenic ulcers to overcome these complications.…”
Section: F I G U R E 6 F O L L O W-u P E N D O S C O P I C I Ma G Ementioning
confidence: 99%
“…Wall emphysema and intestinal pneumatosis have been described, but these conditions are usually reversible [58] . More serious adverse events described after APC treatment are asymptomatic antral stenosis [59] and upper GI hemorrhage. One severe case of sepsis, which conduced to death due to infectious peritonitis, has also been described [60] .…”
Section: Endoscopic Treatmentmentioning
confidence: 99%